The Effect of Integrative Learning Based on Islamic Values on The Religious Attitudes of Elementary School Students - Silfa Devi Safitri; Muhlasin Amrullah; Khizanatul Hikmah (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This study aims to determine the effect of integrative learning based on Islamic values ​​on the religious attitudes of elementary school students in Social Studies (IPS). This study uses a quantitative approach with a true experimental design method. The sample consisted of 60 fourth-grade students of SDN Cemandi, the experimental and control groups. The instrument used was a multiple-choice religious attitude test that had been validated and tested for reliability. Data analysis was carried out using SPSS 26. The results of the validity test showed that 24 of the 30 items were valid (r ≥ 0.361) and reliable (α = 0.935). The data were normally distributed and homogeneous. The results of the independent t-test showed a significant difference between the post-test scores of the experimental group (mean = 88.23) and the control group (mean = 82.83) with p = 0.041. The paired t-test also showed a significant increase in the experimental group between pre-test scores (mean = 62.73) and post-test scores (mean = 88.23) with p = 0.000. These results indicate that integrative learning based on Islamic values ​​has a significant effect on improving students' religious attitudes